COVID-19 and terrorism: Assessing the short-and long-term impacts - Silke, Andrew (Pool Re and Cranfield University, 2020)
The COVID-19 pandemic is already having a significant impact on terrorism in a variety of ways. There is a mixed picture on the level of attacks in the short-term – lockdown measures will tend to inhibit attacks but terrorist propaganda calling for attacks (while authorities are distracted, etc.) will incite some incidents. Much propaganda – and particularly that connected to far-right extremism – is focusing on conspiracy theories connected to COVID-19 and this has already inspired plots and attacks. Islamist extremist propaganda is focusing more on the vulnerability of government opponents distracted by the pandemic and the opportunity this presents for attacks. There is a significant current increase in online extremist activity, raising the risk of increasing short-to-medium term radicalisation. There are strong long-term concerns that states weakened by the serious economic consequences of the pandemic will be more vulnerable to the emergence/resurgence of terrorist groups in many parts of the world.
Keywords: terrorism; political violence; Covid-19; pandemic; radicalisation